Natural versus synthetic rubber uptake in tyres - Jones K P (Journal of Natural Rubber Research, 1997)
In the major traditional rubber consuming areas of Europe, North America and Japan natural rubber has become a speciality rubber, in that uptake is greatest in tyres. In some countries in excess of 70;may be consumed in tyres. In economic terms this is both a considerable strength, and yet may present a considerable potential risk. Techno-economic factors which may indfluence the choice of elastomers in tyres and tyre products are examined. These include properties, price and availability. Factors which may influence the future health of the tyre industry, such as increasing environmental concerns, are not ignored.
Keywords: Natural rubber; Synthetic rubber; Tyres